Income Diversification, Lending and Efficiency on Credit Union Financial Performance in Ghana - Amoah, B. (University of Ghana, 2017)
Available global statistics show that credit unions have, and continue to gain more grounds as penetration rates, asset size and savings levels suggest. Yet traditional depository institutions, especially banks, still present strong competition in the areas of revenue generation, lending and efficiency for the credit union industry. Using data on 61 credit unions in Ghana over the period 2008-2014, this thesis analyses the connections between non-loan income, credit union lending and efficiency in the credit union business without leaving out banking sector development. Specifically we analyse the relationship between non-loan income and credit union performance, examine the determinants of non-loan income. Further we examine discretional and non-discretional factors on credit union lending. Finally, we probe into credit union efficiency and assess the intra and extra determinants over the sample period. We employ the random effect, Hausman-Taylor and truncated Tobit panel data models on risk adjusted return on asset and risk adjusted return on equity to assess how credit union factors influence non-loan diversification income and diversification within the liquid-financial investment activities. For credit union lending we use the fixed effect and random effect model to evaluate discretional and non-discretional factors on credit union. For our objective on cost efficiency and technical efficiency we used a two stage method, we first estimate cost efficiency using Tone’s measure in the Data Envelopment Analysis method and technical efficiency in a variable returns to scale setting for the period 2008 to 2014. For the second stage we estimate a Mixed-effects and Two-Limit Truncated University of Tobit regression to examine credit union specific, banking industry and macroeconomic conditions on efficiency. We find empirical support that non-financial income plays a role in diversifying credit union income. There exists a complementing effect on income from combined non-loan income and investment in liquid-financial asset. Our results suggest that in the case of non-financial income, size, liquidity, loan portfolio, resource usage and net worth are important. For liquid-financial investment, liquidity, age, and net interest margin play a critical role. With respect to loan portfolio, discretional factors such as size, return on equity, management quality and solvency positively associate with credit union lending business. On the other hand, factors such as loan loss, non-loan income diversification activities and lending rates negatively relate to credit union loan portfolio. For the non-discretional factors, increase in banking sector inefficiency would imply more loan business for credit unions. The results also show the presence of a non-linear inverted U-shaped relationship between credit union lending and the size of the credit union. Credit unions’ cost efficiency averaged 38.9 percent whiles average technical efficiency level was 54.4 percent. These efficiencies are mostly influenced by internal factors and the banking industry. A monopolized and inefficient banking sector does not challenge efficiency improvement in the credit union industry. We also find that technical efficiency does not necessarily translate into cost efficiency for credit unions. We recommend that if management’s goal is diversification, then non-financial income is the best option to pursue against investment in liquid-financial asset, especially for smaller sized credit unions. On the other hand, if the objective is to supplement income, then management should consider liquid-financial investment irrespective of the size of the credit union. Credit union managers should monitor developments taking place in the loanable funds market as banks’ increasing overhead cost may mean a possible increase in loan demand in the credit union. Additionally, managers of credit unions should increase loan portfolio carefully so as not to experience any diseconomies of scale from the loan business. We suggest that when targeting cost efficiency, credit union managers should make technical efficiency a priority. Also credit union managers should observe and monitor the activities of the big banks, since their activities have an implication for the adoption of strategies that would help improve overall efficiency in the credit union.
Keywords: Income Diversification; Lending and Efficiency; Credit Union; Financial Performance in Ghana